Factors Affecting the Healthy Lifestyle Implementation: A Case Study in Klampok Lor Village, Demak, Jawa Tengah - Purnomo, Muhammad; Tristanti, Ika; Hartinah, Dewi; Setyaningrum, Yuli (The Indonesian Institute of Science and Technology Research, 2023)
This research investigates the factors affecting the implementation of Health Regulation (No. 2269/2011) within families in Klampok Lor Village, Kebonagung, Demak. The study examines the relationships between maternal education levels, family income, family decision-making, and Clean and Healthy Living Behavior (CHLB) as specified by the regulation. The research employs a cross-sectional approach, gathering data through questionnaires distributed to 85 respondents within the village. The key findings indicate that most mothers in Klampok Lor Village possess only a primary education level, with a minority having advanced education. Family income levels predominantly fall below the Minimum Regional Wage (UMK). Moreover, most families in the village make decisions jointly between spouses. However, implementing Health Regulation within families shows room for improvement, with the majority demonstrating less satisfactory compliance. The research reveals significant relationships between maternal education, family income, decision-making, and CHLB compliance. Mothers with advanced education tend to exhibit better compliance with the regulation, emphasising the role of education in improving health outcomes. Families with higher incomes are more likely to follow CHLB, while collaborative decision-making within families contributes to enhanced compliance. This research underscores the complex interplay of socioeconomic factors, decision-making processes, and health regulation adherence within families. It emphasises the importance of education, economic support, and collaborative decision-making in promoting healthier practices. These findings can inform targeted interventions to bridge socioeconomic gaps and enhance health practices in Klampok Lor Village and similar communities.